2023
DOI: 10.21123/bsj.2022.7599
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Some Heavy Metals, Their Fate and Transportation in Water, Sediment, and Some Biota within AL-Musayyib River, Babylon Governorate, Iraq

Abstract: This study estimated seven heavy metals (Fe, Cu, Zn, Pb, Ni, Cd, Cr) in water (dissolved and particulate phase), sediments and some aquatic organisms including two species from aquatic plants (Ceratophyllum demersum&Phragmites australis); one species of clam (Psedontopeses euphratics) and two species from fish (Oreochromis aureus& Leuciscus vorax)in four sites within Mashroo AL-Musayyib channel project/ branch of Euphrates river, Babylon , medial of Iraq . This aims to show the concentration of these elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Upon comparing our data with that presented in Table (6), we observed that our results fall within the range of values reported in other studies conducted in the region.…”
Section: Locationssupporting
confidence: 90%
See 1 more Smart Citation
“…Upon comparing our data with that presented in Table (6), we observed that our results fall within the range of values reported in other studies conducted in the region.…”
Section: Locationssupporting
confidence: 90%
“…These activities release heavy metals into the environment, leading to contamination of water sources, soil, and air. Therefore, it is crucial to regulate and monitor the discharge of these pollutants to minimize their impact on the environment and human health [6].…”
Section: Introductionmentioning
confidence: 99%